Amino acid substitutions in PBP3 in Haemophilus influenzae strains, their phenotypic detection and impact on resistance to β-lactams - Jakubu, Vladislav; Cechova, Marketa; Musilek, Martin; Malisova, Lucia; Zapletalova, Barbora; Zemlickova, Helena (The Journal of antimicrobial chemotherapy, 2025)
BACKGROUND: Data from surveillance on antibiotic resistance have shown an increasing prevalence of non-enzymatic resistance (β-lactamase-negative ampicillin-resistant) to β-lactam antibiotics among H. influenzae strains in the Czech Republic. Aminopenicillins are recommended agents for non-invasive Haemophilus influenzae infections. The phenomenon of non-enzymatic resistance to β-lactams is complicated by the fact that the phenotypic detection of PBP3 with specific amino acid substitutions (rPBP3) is challenging, since rPBP3 isolates have repeatedly been demonstrated to be split by the epidemiological cut-off values (ECOFF) for aminopenicillins defined by EUCAST. OBJECTIVES: We sought to determine whether the penicillin disc has sufficient detection ability to predict the non-enzymatic mechanism; whether other antibiotics can be used for detection; and what is the agreement between the broth microdilution and disc diffusion methods. METHODS: We undertook susceptibility testing of selected antibiotics according to EUCAST of 153 rPBP3 strains, and sequencing of the ftsI gene to determination amino acid substitutions. RESULTS: For a selected set of rPBP strains: (i) the detection capability for penicillin, ampicillin, cefuroxime and amoxicillin/clavulanate was found to be 91.5%, 94.4%, 89.5% and 70.6%, respectively; (ii) the categorical agreement between the disc diffusion method and the MIC for ampicillin and cefuroxime was 71.1% and 83.8%, respectively. CONCLUSIONS: We observed better recognition of rPBP3 strains by the ampicillin disc than by the penicillin disc. There is frequently a discrepancy in the interpretation of susceptibility results between the methods used.
Keywords: hemofilové infekce; Microbial Sensitivity Tests; beta-laktamová rezistence; Amino Acid Substitution; Humans; beta-laktamy; beta-Lactam Resistance; Sequence Analysis, DNA; Haemophilus influenzae; mikrobiální testy citlivosti; Phenotype; lidé; antibakteriální látky; Penicillin-Binding Proteins; bakteriální proteiny; sekvenční analýza DNA; Anti-Bacterial Agents; substituce aminokyselin; Haemophilus Infections; fenotyp; Czech Republic; Bacterial Proteins; beta-Lactams; Česká republika; proteiny vázající penicilin